The German Federal Supreme Court's Judgment in Booking.com as a Case Study of the Limitations of Competition Law - Francisco E. Beneke Avila (IIC - International Review of Intellectual Property and Competition Law, 2022)
The German Federal Supreme Court (BGH) held that the use of narrow price parity clauses (NPCs) between Booking.com and hotels infringed Art. 101 Treaty on the Functioning of the European Union (TFEU), confirming the Federal Cartel Office's decision. The Supreme Court based its judgment mainly on the following grounds: (1) the use of these clauses restricts intra and inter-brand competition between hotels; (2) NPCs cannot be considered an ancillary restraint in the sense of Art. 101(1) TFEU; and (3) avoiding free-riding through these clauses cannot be considered as a justifying efficiency in the present case under Art. 101(3) TFEU. The present comment focuses on the analysis of the Court regarding (3) and argues that the reasoning in the judgment made conceptual mistakes and statements against settled EU law. The case shows the difficulties the Court~had in handling a case where dynamic considerations are important.~Therefore, even though the Court may have had valid concerns regarding NPCs, the judgment at hand is a step in the wrong direction regarding the judicial function of guidance of undertakings throughout the economy that wish to comply with competition law.
Keywords: 340; EU competition law; Antitrust law; Most favored nation clauses; Narrow price parity clauses; Competition law compliance; Antitrust in the digital economy